2020
DOI: 10.1007/s12230-020-09762-8
|View full text |Cite
|
Sign up to set email alerts
|

Broadening Genetic Diversity of the Japanese Potato Gene Pool

Abstract: Newly developed potato varieties in Japan have never replaced existing old varieties, indicating genetic poverty in our gene pool. To broaden the genetic diversity, Andean primitive cultivated potatoes (Andigena) were used to create parental clones. A total of 184 Andigena accessions and 10 tetraploid Solanum tarijense-Andigena hybrid clones were crossed with a breeding clone 10H17. From 6939 F 1 hybrid clones, 287 were selected as long-day-adapted F 1 clones. From progeny evaluation using these as pollen pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The analysis of the population structure of the potato genetic breeding collection at the Universidad de Nariño based on the Bayesian analyses of the STRUCTURE and PCA program identified two and three possible subpopulations associated with the ploidy level, where diploid genotypes separated from tetraploids, and, according to the geographical origin, the tetraploid genotypes of Colombia separated from those of Peru. Multiple studies have described the use of molecular markers to classify and separate potato genetic materials conserved in germplasm banks according to their ploidy level [ 17 19 , 42 , 43 ] and the degree of genetic breeding to discriminate materials according to the varieties, cultivars, elite materials, wild species and/or related species [ 17 , 42 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the population structure of the potato genetic breeding collection at the Universidad de Nariño based on the Bayesian analyses of the STRUCTURE and PCA program identified two and three possible subpopulations associated with the ploidy level, where diploid genotypes separated from tetraploids, and, according to the geographical origin, the tetraploid genotypes of Colombia separated from those of Peru. Multiple studies have described the use of molecular markers to classify and separate potato genetic materials conserved in germplasm banks according to their ploidy level [ 17 19 , 42 , 43 ] and the degree of genetic breeding to discriminate materials according to the varieties, cultivars, elite materials, wild species and/or related species [ 17 , 42 , 44 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the Euclidean distance was the most reliable, as the other distance measures sometimes showed a decrease in prediction accuracy as sample size increased, which is not expected. Other tetraploid studies have used the Euclidean distance as a tool to measure sub-population distinction, including potato (Hosaka and Sanetomo, 2020;Selga et al, 2022) and marram grass (Hol et al, 2008).…”
Section: Training the Modelmentioning
confidence: 99%
“…Moreover, with the biological features making hereditary improvement in potato was more complexity than in other staple crops, a powerful and effective approach conducted by potato breeders was the unique capacity of among ploidy and wild relative potato to cross as a way to introgress favorable agronomic traits derived from their genetic pools into the aim of the potato breeding strategies [110] [111]. For instance, the genetic diversity of Japanese potato cultivar was broadened by breeding with Andigena [112]. In another study, QTL associated with disease such Early Blight in tetraploid potato was identified in specific chromosomes [113].…”
Section: Prospect Of Polyploidy Potato Is a Main Non-grain Staple Foodmentioning
confidence: 99%